AKTIVITAS ANTIOKSIDAN DAN ANALISIS KIMIA EKSTRAK DAUN JUNGRAHAB (Baeckeafrutescens L.) - Murningsih, Tri (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Extraction of Jungrahab (Baeckea frutescens L.) leaves was done by using organic solvent (ether). The antioxidant activity of the extract was investigated using l,l-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. Ascorbic acid (vitamin C) was employed as a positif control. By virtue of their hydrogen donating ability, the extract and ascorbic acid exhibited reducing power.The extract was found has activity in free radical scavenging activity against DPPH. The antioxidant activity was supposed to be due to the composition of certain constituens e.g. 2,6-di(/-buthyl)-4-hidroxybenzoie acid (BHT-acid), 5,7-dihydroxy-6-methylflavanone and a-tocopherol (vitamin E) within the extract.